2005
DOI: 10.1176/appi.ajp.162.12.2344
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Dependence in Combination With a Family History of Alcoholism as a Predictor of Continued Use of Caffeine During Pregnancy

Abstract: Caffeine-dependent women with a family history of alcoholism were not able to follow their physician's advice to reduce or eliminate caffeine consumption during pregnancy, despite their wanting to do so. This subgroup may require more intensive intervention to ensure caffeine abstinence and may be at greater risk for abuse of or dependence on other drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
2
40
0
2
Order By: Relevance
“…Other clinical studies provide further support for the contention that caffeine use can cause functional impairment and be sufficiently distressing such that individuals will seek treatment and that even those motivated to quit can have difficulty achieving and maintaining abstinence [18,22]. One study involving pregnant women found that caffeine dependence along with a family history of alcoholism predicted cigarette smoking and greater failure at following physicians' instructions to eliminate caffeine during pregnancy [21].…”
Section: Problematic Caffeine Usementioning
confidence: 98%
“…Other clinical studies provide further support for the contention that caffeine use can cause functional impairment and be sufficiently distressing such that individuals will seek treatment and that even those motivated to quit can have difficulty achieving and maintaining abstinence [18,22]. One study involving pregnant women found that caffeine dependence along with a family history of alcoholism predicted cigarette smoking and greater failure at following physicians' instructions to eliminate caffeine during pregnancy [21].…”
Section: Problematic Caffeine Usementioning
confidence: 98%
“…In structured telephone interviews with current caffeine users in Vermont, Hughes and colleagues 12 found that 30% were dependent on caffeine by using DSM-IV criteria adopted for caffeine. Although the sample size was quite small, Svikis et al 29 reported that 57% of 44 women seeking prenatal care from a private obstetrician fulfilled DSM-IV criteria for dependence on caffeine sometime during their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Twin studies suggested a common genetic factor underlies the use of caffeine, alcohol and nicotine, 33,34 although other recent twin studies found that caffeine and nicotine use and dependence were substantially influenced by genetic factors unique to these drugs. 35,36 Also, in a study of pregnant caffeine-using women, 29 those who had a caffeine dependence diagnosis were almost nine times more likely to report a history of daily cigarette smoking, compared with women without the diagnosis. Furthermore, women with both % who met adopted criteria for caffeine dependence In second and third rows, dependence is based on all seven DSM-IV-TR dependence criteria **p < 0.10 (chi-square from 2 · 2 table with drug dependence and no drug dependence vs. caffeine dependence and no caffeine dependence).…”
mentioning
confidence: 99%
“…Svikis et al [117] Women seeking obstetrical care in an office-based practice completed questionnaires and provided saliva samples at three prenatal visits occurring 2-3, 3-4, and 7 months post-conception. On visit 1, the patients received the physician's instructions to stop using caffeine.…”
mentioning
confidence: 99%
“…The evaluation included the Diagnostic Interview Schedule for Children-IV-Youth Version (DISC-IV) and modified DISC-IV questions that assessed caffeine dependence based on DSM-IV substance dependence criteria. Table 5: Prospective epidemiologic studies for caffeine use disorder and the prevalence of the disorder based on DSM-IV criteria [113][114][115][116][117][118][119][120].…”
mentioning
confidence: 99%